PORTEBLE ARTICULATION MIRROR (PAM) AS A MEDIA TO IMPROVE THE THE DEAF CHILDREN’S ABILITY TO USE FACIAL EXPRESSIONS - Erbi Bunyanuddin; Doni Bowo N; Rahayu Rizky P; Rizky Junianto; Muh. Nur Huda (Pelita - Jurnal Penelitian Mahasiswa UNY, 2013)
The purpose of this reaserch is (1) Portable media design and articulationMirror; (2) Mirror articulation tes Portable know the results of the ability of languageexpression deaf children.This type of research is the development of research. A research process: PortablePembuatanrangka articulation Mirror (PAM), making a series of amplifiers, makinga series balancer, merging, testing tools such as pre-test and post-test in children withhearing and ending with evaluation. The instrument used was a questionnaire forusers who include teachers and parents as well as guide books use PAM.The results of this research is to design articulation Portable Mirror (PAM) consistsof power switch, power indicator, Mirror, audio level indicator, Knop treble,volume Knop, Speaker, Knop balance, bass Knop, battery charge indicator, batterycharger Terminal, Port microphone, microphone, and has dimensions of 35 x 21.5 x4.2 cm. Mechanism of action of the PAM PAM works with activated using the powerbutton. To adjust the sound output is set by using the knob-knob (bass, balance,treble, volume). PAM then placed with a distance of 35-55 cm in front of deaf childrenand companion (users).'s Meant to allow users and deaf children to be see each other.PAM can also increase the expression deaf children language skills.